Parsonage–Turner syndrome: a clinical case report - Jesus, Gorete (2008)
Brachial neuritis, Parsonage–Turner syndrome or neuralgic amyotrophy is an acute neuritis of the brachial plexus or isolated nerves, of unknown aetiology, commonly considered an immune mediated inflammatory process against nerve fibres, which has an annual incidence of 1.64 cases per 100,000 population. The authors report the case of a 59 year–old male with a pathological background of hypertension and hyperlipidaemia who developed acute paresis of the right arm, starting on awakening, without any history of trauma or fever. The investigation carried out revealed negative serology for HIV, hepatitis B and C, and VDRL. RMI of the right shoulder detected a dystrophic disorder of the supraspinatus and electromyography showed abnormality of nerve conduction, highly suggestive of Parsonage-Turner syndrome.The authors discuss the differential diagnosis and details of this relatively rare syndrome.